Color shade matching by mobile applications in dental practice: An experimental comparative in-vitro double-blind study - Israa Nafea; Ahmed Alharbi; Abrar Abduh; Abdulaziz Alharbi; Rania M. Moussa (Elsevier, 2019)
Background and aim: Natural tooth shade selection has been a critical step. Over the last decade, computer aided shade matching instruments appeared in market to facilitate shade matching but they presented some disadvantages as increased expenses. Recently, mobile Apps that can analyze color of an image are available. Material and methods: This study is an experimental comparative in-vitro double-blind study. Two mobile Apps were selected to test their ability to match shades of anonymous VITA Classical shade guide tabs as compared to a second set of tabs of the same type. The sample size was convenience n = 16. One of the two shade guides was tested by the two mobile Apps (test tabs). The second shade guide was used as a reference for matching (control tabs). Color readings of the two Apps were recorded in terms of RGB and average values of two examiners were recorded and compared. All tabs in the control shade guide were surveyed searching for the correct matching and percentages of correct matchings were calculated. Reliability of mobile applications was tested after 7 days under similar conditions. Results: A significant difference was found between the two applications in all color ranges (P ≤ 0.05) compared using unpaired t-test. The percentages of correctly matched test tabs with their corresponding control tabs, were 30 and 25%. A significant difference (P ≤ 0.05) was found in RGB values of both applications when comparing repeated RGB readings using paired T-test. Recommendations and conclusion: Mobile applications used differed significantly in reading all color ranges, especially B values. The degree of accuracy was relatively low. A significant difference was reported between multiple readings of the two Apps. Future studies need to focus on producing more specialized dental Apps for shade selection. Keywords shade matching, computer-aided, shade selection, mobile Apps, RGB.